1982
DOI: 10.1002/jsfa.2740330607
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study of bread staling by differential scanning calorimetry. The effect of loaf specific volume

Abstract: Changes in the starch fraction of bread at 21°C have been measured as a function of loaf specific volume using differential scanning calorimetry (DSC). Data from five bakes were fitted by Avrami equations 4 = exp ( A n ) (where 4 is the fraction of the total thermal change still to occur) using an iterative non-linear least squares procedure which enabled simultaneous estimation of limiting value, rate constant ( k ) and Avrami exponent (n). The method allowed the fit of a number of different models to be test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…II) was found to be consistent with, although at the upper end of, the range of published data [2,7].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…II) was found to be consistent with, although at the upper end of, the range of published data [2,7].…”
Section: Resultssupporting
confidence: 83%
“…E x p e rimental data from the DSC and NIR measure m e n t s were analysed separately by fitting an Avrami equation to each data set and comparing the fits statistically [2,7].…”
Section: Data Treatmentmentioning
confidence: 99%
“…The enthalpy values of the retrograded starch reflect the melting of the crystallites formed by the association between adjacent double helices during gel storage (Hoover & Senanayake, 1996), and this endotherm peak was due to the melting of retrograded amylopectin (Abd, Norziah, & Seow, 2000;Fearn & Russell, 1982) rather than amylose. Table 2 lists the changes in retrogradation enthalpy and retrogradation ratio (DH r /DH g ) of gelatinized RS with difference concentrations of TPLs as a function of storage time.…”
Section: Thermal Analysismentioning
confidence: 97%
“…Then recrystallization of amylopectin gradually occurs, followed by gathering of branched chain molecules (Hizukuri, 2000). Fearn and Russell (1982) applied DSC to measure the structural changes of starch in bread during aging. They observed that when staled bread was heated in the DSC, a prominent endotherm peak was present around 50°C, which was absent in the fresh bread, and notably increased with storage time.…”
Section: Effect Of Dextrins On Retrogradation Of Wheat Starchmentioning
confidence: 99%